Investigation of potential bio-active properties and effects on production performance of aquafeed ingredients derived from fish processing waste by way of enzymatic autolysis - Goosen, Neill Jurgens (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD) -- tellenbosch University, 2014.